Visual Degree of Doneness Impacts Beef Palatability for Consumers with Different Degree of Doneness Preferences - Brittany A. Olson; Emily A. Rice; Jessie Vipham; John M. Gonzalez; Lauren L. Prill; Lindsey N. Drey; Michael D. Chao; Michael J. Colle; Phillip D. Bass; Travis O'Quinn (Meat and Muscle Biology, 2019)
The objective of this study was to determine the impact on beef palatability perceptions when consumers with varying degree of doneness (DOD) preferences are served steaks cooked to multiple DOD. Paired Low Choice strip loin steaks were randomly assigned to a DOD of either rare (60°C), medium-rare (63°C), medium (71°C), medium-well (74°C), or well-done (77°C). Consumer panelists were prescreened for DOD preference (rare, medium, or well-done) prior to sensory panels and were assigned to panels based on their DOD preference. In the first round of testing, consumers were served 1 sample from each of the 5 DOD under low-intensity red incandescent light to mask any DOD differences among samples. In round 2 of testing, consumers were fed the paired samples cooked to the same DOD under white incandescent lights. There were no (P > 0.05) consumer DOD preference × steak DOD interactions or consumer DOD preference effects for tenderness, juiciness, and flavor ratings when steaks were evaluated under both lighting types. Within the white-lighting testing, there was a consumer DOD preference × steak DOD interaction (P < 0.05) for overall acceptability. Consumers who preferred steaks cooked to well-done reported no differences (P > 0.05) in overall palatability among DOD under white-lighting, whereas consumers who preferred steaks cooked to rare and medium rated steaks lower (P < 0.05) for overall palatability as DOD increased. Regardless of DOD preference, consumer sensory ratings decreased (P < 0.05) when steaks were cooked above the consumer’s preferred DOD; whereas sensory ratings improved (P < 0.05) when steaks were served below the consumers’ preferences. These results indicate that overcooking steaks has the greatest negative impact on beef palatability perception and thus, foodservice should err on the side of undercooking steaks to preserve, and potentially improve, eating satisfaction.